2007
DOI: 10.1038/sj.cgt.7701022
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of a laminin-derived peptide (SIKVAV) on polymer-modified adenovirus permits tumor-specific targeting via α6-integrins

Abstract: Effective gene therapy for disseminated metastatic cancer is currently impossible because of poor delivery of vector to target sites. Modification of viral vectors to target advanced cancer has long been a challenge. In this study, we aimed to redirect adenovirus tropism to infect prostate cancer cells via a6b1 integrins, whose expression is upregulated during prostate cancer progression. To ablate normal mechanisms of infection and provide a framework for attachment of targeting ligands, viruses were non-gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 45 publications
(52 reference statements)
0
42
0
Order By: Relevance
“…In addition, a peptide SIK-VAV was recently showed to be able to bind to alpha integrin and chemically modified adenoviral vector using SIKVAV peptide could increase gene transfer to alpha integrin positive cells (Stevenson et al, 2007). In the present study, we tested our newly developed system by taking advantage of these small peptides.…”
Section: Generation Of Fiber-modified Adenoviral Vectors Using Prgfmamentioning
confidence: 95%
“…In addition, a peptide SIK-VAV was recently showed to be able to bind to alpha integrin and chemically modified adenoviral vector using SIKVAV peptide could increase gene transfer to alpha integrin positive cells (Stevenson et al, 2007). In the present study, we tested our newly developed system by taking advantage of these small peptides.…”
Section: Generation Of Fiber-modified Adenoviral Vectors Using Prgfmamentioning
confidence: 95%
“…Moreover, coated HAdV vectors induce lower IL-6 levels in serum because of decreased levels of spleen AdV uptake (De Geest et al, 2005). Furthermore, several groups successfully retargeted coated AdV vectors (Parker et al, 2005;Stevenson et al, 2007;Morrison et al, 2008Morrison et al, , 2009Wang et al, 2010). Although in some studies they presented similar levels of antitumoral efficacy (Morrison et al, 2009) or transgene expression (Parker et al, 2005;Stevenson et al, 2007;Morrison et al, 2008;Wang et al, 2010) to unmodified wild-type HAdV-5, others achieved a greater therapeutic effect with negligible side effects (Eto et al, 2010;Yao et al, 2010).…”
Section: Implications Of Antiviral Immune Responses Against Hadv Vectmentioning
confidence: 96%
“…It has been demonstrated that modification of adenoviruses with hydrophilic synthetic polymers based on poly(ethylene glycol) (PEG) (7) or N-(2-hydroxypropyl) methacrylamide copolymer (PHPMA) (8,9) significantly prolongs plasma circulation times and ablates non-specific cell entry. In addition, surface modification of the adenovirus capsid with multivalent polymers provides a platform for retargeting with receptor-specific ligands, such as growth factors (10), tumour-specific peptides (11) or folates (12). However, the covalent attachment of targeting ligand to the coating polymer suffers from several limitations.…”
Section: Abbreviationsmentioning
confidence: 99%